ISLAMIC ETHICS-BASED HUMAN RESOURCE MANAGEMENT IN THE DIGITAL AGE: THE IMPLICATIONS OF HADITH ON STRENGTHENING HUMAN RESOURCES IN THE HALAL INDUSTRY - Akilah, Fahmiah; La Ode Ismail Ahmad,; Muhammadiyah Amin, (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2025)
This study aims to analyze prophetic traditions (hadith) related to Islamic Ethics-Based Human Resource Management (HRM) in the digital era and to examine their implications for strengthening human resources in the halal industry. The research employs a qualitative–descriptive approach through library research and thematic analysis of hadith (mawḍū‘ī), utilizing primary data derived from authentic hadiths, supported by literature on Islamic business ethics and Islamic human resource management. The findings indicate that the principle of ṣidq emphasizes integrity and transparency, amanah highlights moral responsibility, and itqān underscores diligence, precision, and accountability. The integration of these principles forms the foundation of a well-established HRM framework that enhances quality in the halal industry, strengthens an ethical organizational culture, and fosters consumer trust. Thus, the application of Islamic business ethics through values derived from prophetic traditions provides practical contributions to developing a professional, trustworthy, and sustainable halal industry.